INTEGRASI NILAI DALAM PEMBELAJARAN BERBASIS MULTIKULTURAL DI SEKOLAH DASAR - Ratih Rahmawati (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2017)
Values covers everything assumed meaningful for someone’s life in which its considerations are based on the quality of true-false, good-bad, or beautiful-unbeautiful and its orientation is anthropocentric or theocentric. The scope of values taught in formal education is indeed large; therefore the process of realizing the values can run integrally in the educational process. The educational attempts in term of intra-curricular, extracurricular or school’s cultural atmosphere is a place where the values can be integrally implemented in the educational process. The value education is very good to be implanted since the early ages as the prevention of value conflict due to differences in identity, gender, ethnicity, race, and culture. Therefore, value education through multicultural learning should be intensified and as the main subject is elementary school students. With this they are expected to be ready to live in harmony peace and harmony.